Consumption Pattern and Demand Analysis of Dacryodes edulis in Umuahia Metropolis of Abia State (2015)
Consumption pattern and demand analysis of Dacryodes edulis commonly called ube by the Igbos in Umuahia, Nigeria was studied. The various uses and reasons for consumption of Dacryodes edulis, socio- economic characteristics of respondents, income elasticity, and chi square to determine the relationship between Consumption of Dacryodes edulis and some variables that affect it, are addressed. Simple random sampling was adopted. A well-structured questionnaire were used for Dacryodes edulis consumers at the household in two selected local government areas in Umuahia. A total of (160) one hundred and sixty questionnaires were administered, on a total of eight (8) villages in the city of Umuahia. Data obtained were subjected to simple descriptive statistics, which shows that almost all the respondents (92.0%) consume Dacryodes edulis and they got to know of Dacryodes edulis through family and friends due to its high medicinal value as claimed by 91.3% of the respondents. The income elasticity of Dacryodes edulis demand is 13%. The income elasticity is significant at 5% with coefficient of 0.13, this means that a percent increase in income leads to a 13% of change in Dacryodes edulis consumption.